Heart disease genes and SNPs - Humphries, Steve (Henry Stewart Talks, 2024)
The causes and mechanisms of heart disease, Plasma lipid metabolism, Identification of candidate gene, Relevant animal models, Human studies, Proving functionality of candidate SNPs, APOA5 SNP studies, Phenome scans using candidate SNP chips, Novel anti-sense approaches for lipid-lowering